IDHOCNET: A Novel ID Centric Architecture for Ad Hoc Networks - Shahrukh Khalid; Athar Mahboob; Choudhry Fahad Azim; Aqeel Ur Rehman (Journal of Computer Networks and Communications)
Ad hoc networks lack support of infrastructure and operate in a shared bandwidth wireless environment. Presently, such networks have been realized by various adaptations in Internet Protocol (IP) architecture which was developed for infrastructure oriented hierarchical networks. The IP architecture has its known problem and issues even in infrastructure settings, like IP address overloading, mobility, multihoming, and so forth. Therefore, when such architecture is implemented in ad hoc scenario the problems get multiplied. Due to this fact, ad hoc networks suffer from additional problems like IP address autoconfiguration, service provisioning, efficient bandwidth utilization, and node identification. In this paper we present IDHOCNET which is a novel implementation of service provisioning and application development framework in the ad hoc context. We illustrate a number of implemented features of the architecture which include IP address autoconfiguration, identification of nodes by using real world identifiers, IP based services support in ad hoc networks, and a new class of application known as ID based application. Moreover how identifiers can completely replace the IP addresses to run the IP based applications is shown. It is expected that this work will open new research horizons and paradigms for ad hoc networks.